2020
DOI: 10.1039/c9sm01965k
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the fluid–matrix affinity in an organogel from the growth dynamics of oil stains on blotting paper

Abstract: Fluid–matrix affinity in an organogel is characterized by capillarity-induced oil release using absorbing paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Here, I(i, j) and m(i, j) are the transmitted intensity and the mass of oil in the pixel at position (i, j); Ibg is the average background intensity; Apx is the area of a single pixel; c1 and c2 are constants determined by calibration. The details of the calibration procedure can be found in (31). The values of the calibration constants for the bled oils are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, I(i, j) and m(i, j) are the transmitted intensity and the mass of oil in the pixel at position (i, j); Ibg is the average background intensity; Apx is the area of a single pixel; c1 and c2 are constants determined by calibration. The details of the calibration procedure can be found in (31). The values of the calibration constants for the bled oils are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…A possible explanation for the decreased bleeding rate is the partial collapse of the grease matrix after a considerable A c c e p t e d M a n u s c r i p t amount of oil is extracted during the bleeding process. Our earlier work showed that greases with a partially collapsed microstructure bleed significantly slower (31). Similarly, diluting greases with their own base oil, a reverse process of grease bleeding, is also proven to enhance the rate of bleeding (24).…”
Section: Grease Bleeding Behaviourmentioning
confidence: 96%
See 3 more Smart Citations